Tyrannosauraus Rex - Fritz, Sandy and George Olshevsky (Mankato, MN Smart Apple Media, 2003)
Presents information on Tyrannosaurus rex, including physical characteristics, diet, habitat, known social organization, close relatives, and areas where fossils have been found.
Keywords: Tyrannosaurus Rex; Dinosaurs